2016
DOI: 10.1128/jvi.01392-16
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 Induces Phosphorylation and Reorganization of Lamin A/C through the γ 1 34.5 Protein That Facilitates Nuclear Egress

Abstract: Herpes simplex virus 1 (HSV-1) remodels nuclear membranes during virus egress. Although the UL31 and UL34 proteins control nucleocapsid transit in infected cells, the molecular interactions required for their function are unclear. Here we report that the ␥ 1 34.5 gene product of HSV-1 facilitates nucleocapsid release to the cytoplasm through bridging the UL31/UL34 complex, cellular p32, and protein kinase C. Unlike wild-type virus, an HSV mutant devoid of ␥ 1 34.5 or its amino terminus is crippled for viral gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 43 publications
(55 reference statements)
0
49
0
Order By: Relevance
“…Furthermore, a virus lacking 147 amino acids from the N terminus of ICP34.5 failed to control TBK1-dependent interferon responses (18,19). Contained within this N-terminal deletion of ICP34.5 tested by Ma et al in 2012 are regions that are also required for beclin1 and p32 interactions (20,36,46). In this study, we genetically dissected domains of ICP34.5 to evaluate the influence of beclin1 and TBK1 interaction on replication and virulence of the virus.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, a virus lacking 147 amino acids from the N terminus of ICP34.5 failed to control TBK1-dependent interferon responses (18,19). Contained within this N-terminal deletion of ICP34.5 tested by Ma et al in 2012 are regions that are also required for beclin1 and p32 interactions (20,36,46). In this study, we genetically dissected domains of ICP34.5 to evaluate the influence of beclin1 and TBK1 interaction on replication and virulence of the virus.…”
Section: Discussionmentioning
confidence: 94%
“…Given evidence that HSV-1 infected cell protein (ICP) 34.5 is involved in regulation of the interferon system and viral egress (Jing et al, 2004; Wang et al, 2014; Wu et al, 2016), we investigated whether this protein could serve as a viral activator of HPSE. Infection of HCE cells with a mutant virus lacking the γ 34.5 gene was markedly impaired in its ability to upregulate HPSE mRNA expression (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, HSV-1 enzymes may also alter the regulation of PTMs on host proteins and histones. For example, HSV-1 UL13 directly phosphorylates host nuclear lamin proteins and this phosphorylation induces partial lamin disassembly or reorganization that allows virions to reach the inner nuclear membranes (16,17). However, even though a prior study identified phosphorylation on HSV-1 proteins (18), a global picture of regulation of host phosphorylation upon HSV-1 infection has not been fully investigated.…”
Section: Herpes Simplex Virus (Hsv-1)mentioning
confidence: 99%